Interprofessionalism and interprofessional research: a challenge still to be won in Italy - Sarli, Leopoldo; D’Apice, Clelia; Rossi, Sandra; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2019)
Public health and pedagogical institutions have long been calling for collaborative models of assistance and training that provide inter-professional synergy and there is a broad international consensus on the importance of inter-professionalism in the field of assessment and healthcare provision (1-10). [...]